Défis de l’enseignement universitaire dans un contexte multiculturel : une étude de cas en Asie - Loïse Jeannin (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
On the campuses of international universities, student population displays a diversity of cultural, linguistic, and socio-economic backgrounds. This diversity arises from the geographical mobility of students that generates a diversity of learning needs and habits within the classrooms. To teach more effectively in this context of diversity and meet local and international students’ learning needs, some lecturers require continuing education opportunities. This qualitative study focuses on one international university in Thailand where students and lecturers come respectively from 92 and 15 different countries. The two objectives of this study are : (1) to understand students’ learning difficulties as perceived by lecturers and (2) to identify lecturers’ needs for professional development in this multicultural context. Based on a maximum variation sampling strategy, ten lecturers from eight different countries and with varying academic backgrounds, were selected for this study. The lecturers participated in a focus group and/or in an individual interview. Thematic analysis enabled to reveal students’ learning difficulties but also to identify lecturers’ needs and preferences for professional development. Regarding students’ learning issues, lecturers mentioned the diversity of language competencies and some challenges related to group work in multicultural teams. In terms of lecturers’ preparation, participants expressed a desire to increase their knowledge related to differentiated instruction and class management in this intercultural context. Recommendations finally focus on teacher professional development programs and student preparation for multicultural group work.